The Macron Régime : The Ideology of the New Right in France - Devellennes, Charles (Bristol University Press, 2023)
This book examines Emmanuel Macron's political career from his rise as a public figure to his time as a president. By offering a close study of his actions and ideological commitment, this book argues that, despite claims of being ideologically neutral, Macron actually represents a new form of right-wing politics in France.